Left Ventricular Pseudoaneurysm Complicating Acute Inferoposterior Myocardial Infarction: A Case Report - Vijay Yadav; Ratna Mani Gajurel; Chandra Mani Poudel; Manju Sharma; Suman Adhikari (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
Left ventricular pseudoaneurysm is a rare mechanical complication of acute myocardial infarction. The study aims at early detection of a rare complication of myocardial infarction which carries a grave prognosis and whose mainstay of management is surgical. We describe a 60 year old male who presented with typical ischemic type of chest pain with low blood pressure and heart rate. A 12 lead electrocardiogram showed atrioventricular (AV) dissocation with ST segment elevation in the inferior leads. The initial echocardiography depicted moderate pericardial effusion without tamponade. The possibilities of both, acute mechanical complications of myocardial infarction, and acute aortic dissection were sought of. The echocardiography on the following day revealed a free wall rupture of the infero-posterior wall of left ventricle with formation of a pseudoaneurysm. This was further proved by the computed tomography (CT) of chest with contrast, which in addition, ruled out acute aortic dissection. The patient was planned for an early surgery. Pre-operative coronary angiogram revealed complete occlusion of distal left circumflex artery and 70-80% discrete stenosis of mid left anterior descending artery.